RANCANG BANGUN SISTEM PENGAPIAN SEMI ELEKTRONIK DOUBLE TRIGGER SEBAGAI PENGEMBANGAN SISTEM PENGAPIAN KONVENSIONAL - Holik, Hasan; Mujianto, Haris; Rubiono, Gatut (Virtual of Mechanical Engineering Article, 2016)
Technology   development   has   negative   impact   for   convensional  automotive   product.Electronic  system  has  lower  exhaust  emission  than  convensional  system.  Convensional  system still can develop in order to minimize environmental risk. The development of convensional system can be done by changing the system into semi electronic. It is need an addition of CDI DC system and replacement of switch between pulser and trigger. Trigger must made at distributor shaft with high precision working. This research is aimed to develop convensional ignition system into semi electronic to increase the performance of automotive engine.